Kemampuan Kulit Pisang Kepok (Musa acuminate L.) dalam Menurunkan Kadar Timbal (Pb) dalam Air - Vini Widya Ningsih; Rasman Rasman; aNDI Ruhban (Poltekkes Kemenkes Yogyakarta, 2013)
Water is a resource that is absolutely indispensable for life. Based on its utility, the water quality is expected to be within the tolerance limits of proper water criteria. Good water has to meet the health requirements in terms of physical, chemical, bacteriological, and radioactivity condition, in order not to causing disease to humans. One of water problem which is frequently encountered based on the chemical condition is heavy metal pollution, such as lead (Pb), as a result of envi-ronmental pollution. One of the natural methods that can be applied to reduce the heavy metals concentration is utilization of banana peels. The purpose of this research is to determine the abi-lity of kepok banana (Musa acuminate L.) peels in decreasing the Pb level in water by conduct-ing an experiment with pre-test post-test wit control group design. The banana peel filtration me-dia is comprised of two types, i.e. original form of peel cuts and the peels which were processed into granular charcoal form. The Pb polluted water used in this study was obtained from Panam-pu Canal II in Tinumbu Street of Makassar City. The contact time between filtration media and the water was set at 60 minutes, and there were three replications. Results of the study showed that original banana peels medium could reduce Pb concentration in average of 0,0367 mg/l or 87,87 %, while the charcoal formed medium was able to reduce as much as 0,0228 mg/l in ave-rage or 54,54 % reduction.